2004
DOI: 10.1021/ma034604+
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Multiple Melting Endotherms in a High Hard Block Content Polyurethane. 2. Structural Investigation

Abstract: The structure and morphology of a set of high hard block content (50% to 100% hard segment by weight) linear thermoplastic polyurethanes has been investigated mainly via small angle X-ray scattering (SAXS) and transmission electron microscopy (TEM). All the results obtained in this investigation have been correlated to our previous work on the thermodynamic properties of the same set of samples (Saiani et al. Macromolecules 2001, 34, 9059). The soft segment was based on a poly(propylene oxide) polyol end-cappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
128
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 28 publications
8
128
1
1
Order By: Relevance
“…Spherical or cylindrical morphologies [1] have been reported in MDI extended with ethylene diamine, while a morphology without a specific shape was reported for MDI extended with 2-methyl-1,3-propane diol [2] or with butane diol [3]. The TPU morphology affects the mechanical properties [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spherical or cylindrical morphologies [1] have been reported in MDI extended with ethylene diamine, while a morphology without a specific shape was reported for MDI extended with 2-methyl-1,3-propane diol [2] or with butane diol [3]. The TPU morphology affects the mechanical properties [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The TPU nanomorphology is commonly visualised by Atomic Force Microscopy (AFM) [8][9][10] or Transmission Electron Microscopy (TEM) [2,5]. However, as these techniques are 1…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that structural units of various forms and sizes develop during polymerization [13][14][15]. Besides a crystalline or at least highly ordered phase, soft and hard segments form corresponding phases which are partially soluble in each other [16][17][18][19][20][21]. Solubility depends very much on the interaction of the components, the urethane groups are capable of forming specific interactions, H-bonds with each other, but also with the soft segments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Both drop-matrix (Figure 1a and 1d) and co-continuous (Figure 1b and 1c) morphologies can be recognized: in the former, isolated domains (dark) of the soft phase are suspended in the hard matrix (bright); in the latter, the phases are both continuous and appear interpenetrated. Further quantitative information can be collected through SAXS analysis, which is often employed when dealing with polyurethane systems [8,18]. The one-dimensional SAXS patterns of intensity I(q) vs. q of the various TPUs are shown in Figure 2.…”
Section: Microstructural Analysesmentioning
confidence: 99%
“…Less intensive and broader peaks are instead noticed for the other samples, suggesting more homogeneous structures in which ordered crystalline and/or para-crystalline hard domains appear randomly dispersed in a continuous soft matrix. An approximate estimate of the average inter-domain distance can be inferred from the position of the intensity peak [18]. The data, computed by means of the Bragg's law, are listed in Table 2.…”
Section: Microstructural Analysesmentioning
confidence: 99%